2017
DOI: 10.1002/imhj.21641
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Opening My Arms Rather Than Pushing Away:” Perceived Benefits of a Mindfulness-Based Intervention Among Homeless Women and Young Children

Abstract: Family homelessness is associated with adverse outcomes in mothers and their young children. Evidence-based programs are needed to support the socio-emotional needs of these families. The purpose of this qualitative study was to explore the perceived benefits of participating in a mindfulness program in mother-child dyads receiving services at a therapeutic nursery serving homeless children under the age of 3. A convenience sample of 17 predominantly African American mothers participated in in-depth qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Mothers expressed feelings of pride when they observed positive changes in their children’s health and social outcomes after participating in maternal programs. They felt that family-oriented interventions allowed them to become effective mothers [54,66,71,82]: “It’s awesome because it makes me feel like I’m doing the right thing you know, that I’m being a good parent”. [54]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mothers expressed feelings of pride when they observed positive changes in their children’s health and social outcomes after participating in maternal programs. They felt that family-oriented interventions allowed them to become effective mothers [54,66,71,82]: “It’s awesome because it makes me feel like I’m doing the right thing you know, that I’m being a good parent”. [54]…”
Section: Resultsmentioning
confidence: 99%
“…Individuals participating in housing programs initially felt socially isolated but found that support from peers and staff with shared lived experience of marginalization allowed them to develop strong connections with and eventual feelings of altruism toward their peers. [58,60,62,67,68,72,76,84] The key relationships identified were with staff,[62,66,72,73,86] peers, [56,64,67,69,84] friends,[64] family,[54,66,69] people from their cultural community,[60,72] and the broader community. [67,72] These individuals also found that the peer support in youth- and women-specific programs was especially beneficial to the development of relationships and in enhancing one’s commitment to seek treatment and participate in programs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an adjunct to the more basic interventions, these types of training and personal support interventions can have value for some people who are homeless (Milby et al 2010). Some research has also provided preliminary explorations of the benefits of mindfulness training for people who have experienced homelessness (Alhusen et al 2017;Maddock et al 2017).…”
Section: Descriptionmentioning
confidence: 99%